Phylogenetic relationship of some “accessory” helicases of plant positive-stranded RNA viruses: toward understanding the evolution of triple gene block - Morozov, Sergey Y.; Solovyev, Andrey G. (Frontiers in Microbiology, 2015)
Recently, we hypothesized that silencing suppression activity gained by a viral replicative helicase led to the emergence of the second helicase possessing activity of the viral silencing suppressor and/or movement protein (MP). Our hypothesis accounted for the evolutionary origin of the specialized ‘triple gene block’ (TGB) in plant virus genomes encoding the MPs TGB1, TGB2, and TGB3 required for viral cell-to-cell transport through plasmodesmata. Here, we used public transcriptome databases to identify previously unrecognized viruses. The analysis of novel viral genomes further supported the previously proposed scenario of TGB origin and evolution, which included the following steps. First, the accessory helicase gene could have been acquired by horizontal gene transfer (HGT) presumably occured independently in different virus groups. Second, the TGB2 gene evolved by HGT or autonomization of the C-terminal transmembrane domain found in at least one TGB1 helicase. Third, the TGB3 gene has most likely emerged in the genomic block consisting of the TGB1 and TGB2 genes.